2016
DOI: 10.1080/00480169.2016.1259594
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance patterns of bacteria isolated from canine urinary samples submitted to a New Zealand veterinary diagnostic laboratory between 2005–2012

Abstract: The results of this study provide important regional information regarding the prevalence of bacterial uropathogens and their susceptibility patterns. There was an increase in resistance to some commonly used antimicrobials in the treatment of urinary tract infections. Having access to regional antimicrobial susceptibility results is crucial when forming guidelines for the use of antimicrobials for the treatment of urinary tract infections. Given changes in practising habits and antimicrobial usage over time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 15 publications
10
32
1
1
Order By: Relevance
“…E. coli was the most frequently isolated uropathogen in this study with a prevalence similar to that reported elsewhere (35%–70%) 3 6 13 15 18 19. The prevalence of Staphylococcus sp.…”
Section: Discussionsupporting
confidence: 88%
“…E. coli was the most frequently isolated uropathogen in this study with a prevalence similar to that reported elsewhere (35%–70%) 3 6 13 15 18 19. The prevalence of Staphylococcus sp.…”
Section: Discussionsupporting
confidence: 88%
“…Close contact within the home, between partners, parents and children, and between pets and their owners may be a factor in the transmission of the MDR bacteria isolated in this study. In New Zealand, clinical infections with MDR E. coli occur in pets, but at rates that are unknown and assumed to be low [8,49]. Interestingly, isolates of E. coli collected from dog fecal samples in two different households had unique fecal AMR E. coli, all of which were a different ST from the clinical case.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Clavulansäure fördert die Selektion von so genannten pAmpC-Resistenzen und Keime mit diesem Resistenzgen sind gegen Cephalosporine der 1. bis 3. Generation unempfindlich (Karkaba et al, 2017;McMeekin et al, 2017 (Sigel et al, 1981b). gestörtem Allgemeinbefinden mit Zeichen einer Sepsis und/oder SIRS (systemic inflammatory response syndrome) indiziert ist.…”
Section: Therapie Von Harnwegsinfektionenunclassified